Systematic Literature Review: Knowledge management in executive engineering projects using Building Information Modeling (Advances in Knowledge Representation, 2023)
The construction phase is the most important of a project cycle and, in this direction, capturing tacit knowledge in such a complex environment is a concern for knowledge management. When talking about the Architecture, Engineering and Construction industry, knowledge capture is often lost. In projects, the turnover of people is high and the inability to manage knowledge ends up implying loss of knowledge and risk of repeating mistakes. In view of this context, the objective of this research was to carry out a rigorous systematic review of the literature, which enabled the creation of search strings, document selection and systematization of selected research following the Kitchenham protocol (2007) that correlates the current processes recommended by the Brazilian Society of Knowledge Management with the main activities of Building Information Modeling being the result of the research a simplified summary model that facilitates the understanding of the preservation of knowledge in executive projects.